Herausforderung Medien: Zwischen Freiheit und Zwang. (Duncker & Humblot GmbH, 2021)
The media are a vivid example of technical-institutional interdependencies: in the course of the market dynamics driven by technical innovations, traditional institutional arrangements become obsolete, which creates new regulatory challenges. But if the media form a "fourth estate," then the rapid process of change cannot be answered with "laisser faire." The regulatory challenge is therefore particularly great for the media and requires careful scientific reflection. The "Competition Working Group of the Economic Policy Committee" in the Association for Social Policy discussed this tension between freedom and coercion in detail with representatives from politics, associations and business practice. The conference proceedings contain the presentations and additional contributions: Dr. Werner Hippe, President of the Association of German Magazine Publishers e. V., Bonn, illustrates the opportunities and risks for magazine publishers in view of the changed technical possibilities. Peter Voß, director of Südwestdeutscher Rundfunk, Baden-Baden, discusses the current and future legitimacy of public service broadcasting in a changing environment. Reinhard Klimmt, MdL, chairman of the media commission of the SPD federal board, talks about the social design potential of media policy. Prof. Dietrich Ratzke develops a fundamental criticism of the euphoric scenarios of the media future. Prof. Dr. Wolf-Dieter Ring, President of the Bavarian State Center for New Media, Munich, and Dr. Norbert Schneider, Director of the State Broadcasting Authority of North Rhine-Westphalia, Düsseldorf, go into the different experiences in the respective federal states.